Relapsing Peritonitis in children who undergo chronic peritoneal dialysis: a prospective study of the International Pediatric Peritonitis Registry - Lane, Jerome; Warady, Bradley A.; Feneberg, Reinhard; Majkowski, Nancy L.; Watson, Alan R.; Fischbach, Michel; Kang, Hee Gyung; Bonzel, Klaus E.; Simkova, Eva; Stefanidis, Constantinos J.; Klaus, Günter; Alexander, Steven R.; et al. (Clinical journal of the American Society of Nephrology, 2010)
Background and objectives: The International Pediatric Peritonitis Registry (IPPR) was established to collect prospective data regarding peritoneal dialysis (PD)-associated peritonitis in children. In this report, we present the IPPR results that pertain to relapsing peritonitis (RP). - Design, setting, participants, & measurements: This was an online, prospective entry into the IPPR of data that pertain to peritonitis cases by participating centers. - Results: Of 490 episodes of nonfungal peritonitis, 52 (11%) were followed by a relapse. There was no significant difference between RP and non-RP in distribution of causative organisms and antibiotic sensitivities. Initial empiric therapy—ceftazidime with either first-generation cephalosporin or glycopeptide (vancomycin or teicoplanin)—was not associated with relapse. Switching to monotherapy with a first-generation cephalosporin on the basis of culture results was associated with higher relapse rate (23%) than other final antibiotic therapies (0 to 9%). Culture-negative RP was less likely to have a satisfactory early treatment response than non-RP (82 versus 98%). Young age, single-cuff catheter, downward-pointing exit site, and chronic systemic antibiotic prophylaxis were additional independent risk factors for RP in the multivariate analysis. Compared with non-RP, RP was associated with a lower rate of full functional recovery (73 versus 91%), higher ultrafiltration problems (14 versus 2%), and higher rate of permanent PD discontinuation (17 versus 7%). - Conclusions: This is the largest multicenter, prospective study to date to examine RP in children. In addition, this is the first report in the literature to examine specifically the relationship of postempiric antibiotic treatment regimens to the subsequent risk for relapse.